2015
DOI: 10.1039/c5py01377a
|View full text |Cite
|
Sign up to set email alerts
|

Robust, highly elastic and bioactive heparin-mimetic hydrogels

Abstract: We construct robust, highly elastic, and bioactive graphene oxide doped heparin-mimetic hydrogels for use in drug delivery and other potential biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 66 publications
1
8
1
Order By: Relevance
“…Besides the robust and elastic mechanical properties, the in situ polymerization of vinyl monomers may also introduce multifunctional and biocompatible hydrogels. Cheng and Zhao et al have synthesized heparin-mimetic hydrogels via an one-pot in situ polymerization, Figure . In the heparin-mimetic hydrogel, GO is covalently doped into the networks of heparin-mimetic matrix due to the cross-linking between the initiated macromolecular radicals and sp 2 bonds of GO.…”
Section: Fgns-based 3d Architecturesmentioning
confidence: 99%
“…Besides the robust and elastic mechanical properties, the in situ polymerization of vinyl monomers may also introduce multifunctional and biocompatible hydrogels. Cheng and Zhao et al have synthesized heparin-mimetic hydrogels via an one-pot in situ polymerization, Figure . In the heparin-mimetic hydrogel, GO is covalently doped into the networks of heparin-mimetic matrix due to the cross-linking between the initiated macromolecular radicals and sp 2 bonds of GO.…”
Section: Fgns-based 3d Architecturesmentioning
confidence: 99%
“…Thus, the PAA hydrogels were formed by being attached to the GO skeleton by hydrogen bonds, and the obtained GO-PAA HPs showed a special hierarchical pore structure, which was totally different from the GO and PAA hybrids prepared by common blending methods. 37 Moreover, it was found that the pore walls of the GO-PAA HPs were much thinner than those of the PAA HPs, which might be attributed to the regulating effect and the super large specific surface area of the GO skeleton. For the GO-PAA25, with the same PAA content as PAA25, the thickness of the pore walls ranged from 347 to 599 nm, which was over 12 times thinner than that of PAA25.…”
Section: Resultsmentioning
confidence: 99%
“…This special pore structure might be explained as follows: GO sheets could be self-assembled into a porous network by the π–π stacking interaction and van der Waals forces; the high-strength PES template could provide a protective shell for the enwrapped GO aqueous solution, which could maintain the porous network during the process of mixing GO with AA. Thus, the PAA hydrogels were formed by being attached to the GO skeleton by hydrogen bonds, and the obtained GO-PAA HPs showed a special hierarchical pore structure, which was totally different from the GO and PAA hybrids prepared by common blending methods . Moreover, it was found that the pore walls of the GO-PAA HPs were much thinner than those of the PAA HPs, which might be attributed to the regulating effect and the super large specific surface area of the GO skeleton.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33] These functional polar groups enable easy dispersion of GO in many solvents to prepare GO doped sulfonated polyanion hydrogels. 34,35 It was also reported that GO showed good biocompatibility and could serve as a promising candidate for diverse biomedical applications. 36,37 Furthermore, GO also exhibited good compatibility with PES due to the hydrophobic interaction and π-π interaction.…”
Section: Introductionmentioning
confidence: 99%